Carcinoma Telangiectaticum of Unknown Primary - Cicek, Demet; Kandi (Coskun), Basak; Demir, Betuel; Dagli, Ferda; Gedik, Fatma (Deri Zuhrevi Hastaliklar Dernegi, 2008)
Carcinoma telangiectaticum is an unusual type of cutaneous metastasis originating from various malignant tumors and characterized by telangiectases. This disorder appears with the spread of malignant cells to the skin via superficial lymphatics. It presents as small pink to purplish pseudovesicles, purpuric papules, plaques and telangiectases. A 58-year-old female patient with extensive internal organ metastasis, the primary of which could not be determined, was consulted for bluish lesion on her abdomen, while she was receiving cisplatinum and etoposide combination chemotherapy and radiotherapy. Histopathologic examination revealed that the superficial lymphatics in dermis were attacked by tumoral cells. Final diagnosis was established by clinical and histopathological findings as carcinoma telangiectaticum due to metastasis of a malignant tumor of unknown origin. Unfortunately our patient succumbed during her chemotherapy. (Turkderm 2008; 42: 70-2)
Primeri belli olmayan bir karsinoma telanjiektatikum
Keywords: Carcinoma Telangiectaticum